Prediksi Erosi dengan Metode Universal Soil Loss Equation (USLE) di DAS Kerandangan Kabupaten Lombok Barat - Yuliana, Yuliana; Aji, Irwan Mahakam Lesmono; Sari, Diah Permata (Fakultas Kehutanan Universitas Mulawarman, 2025)
Kerandangan Watershed is frequently affected by flooding despite more than 50% of its area being covered by forest land. To assess the potential erosion in the Kerandangan Watershed, calculations were conducted using Universal Soil Loss Equation (USLE) method. Erosion Hazard Level is classified based on soil depth and erosion rate. The research findings serve as fundamental data for managing the Kerandangan Watershed. The results indicate a potential erosion rate ranging from 0.14 to 1,113.92 tons/ha/year, with highest potential erosion occurring in the shrub land unit-slope V (SV) and lowest in the forest land unit-slope I (HI). Erosion Hazard Level in the Kerandangan Watershed is classified as follows: Very Light Erosion Hazard is found in forest land units (HI, HIII, HIV, and HV), covering 69% of the total watershed area. Light Erosion Hazard is present in orchard land units (KI) and field land units (LI), covering 17%. Moderate Erosion Hazard is observed in orchard land units (KII), covering 1%. High Erosion Hazard is identified in orchard land units (KIII, KIV), field land unit (LIV), and shrub land unit (SIII), covering 9%. Very High Erosion Hazard is found in shrub land units (SIV, SV), covering 2% of the total area.